INVESTIGATION OF PENETRATION AND PENETRATION INDEX IN BITUMEN MODIFIED WITH SBS AND REACTIVE TERPOLYMER - Keyf, Seyfullah (YILDIZ TECHNICAL UNIV, 2010)
The aim of this work is to develope properties of bitumen in asphalt which modifying is applied on road in city. In order to reduce the sensitivity of bitumen against to temperature and to increase service-life of over structure was formed new asphalt composition. ELVALOY RET, elastomeric reactive terpolymer, which was developed by DUPONT company was used as a new additive. With addition of Elvaloy RET and SBS in bitumen, the values of penetration decreased, penetration index increased in final product according to binding with pure bitumen.
Keywords: Modified bitumen; elastomeric reactive terpolymer; SBS; Engineering